Estudio de factibilidad en la inversión y comercialización de jalea de banano en el cantón la Maná, provincia de Cotopaxi - Zambrano Jaramillo, Janeth Alexandra (2012)
This thesis project was conducted with the aim of encouraging and promoting the production and marketing of Banana, are researched and developed in the Canton La Maná, Cotopaxi Province. We analyzed many years that man has been creating and perfecting different techniques to source raw materials during any season. I bring this factor to the decision to create a company that offers Micro power alternative based on natural fruit rich in carbohydrates and vitamins, such as the banana jelly. To this was adopted, several data collection methods, one of which was the survey direct product suppliers, consumers and experts possible nearby, also took into account a reference of 10,554 families is what has taken a sample population of 384 families, turn the easy collection and handling of raw material in this case bananas, contributes significantly to the positive development project but we must be very cautious in data collection and analysis for the same, since it depends on factors of production is obtained.